Role of the putative N-glycosylation and PKC- phosphorylation sites of the human sodium-dependent multivitamin transporter (hSMVT) in function and regulation - Ghosal, Abhisek (2011)
The sodium-dependent multivitamin transporter (SMVT) is a major biotin transporter in a variety of tissues including the small intestine. The human SMVT (hSMVT) polypeptide is predicted to have four N-glycosylation sites and two putative PKC phosphorylation sites but their role in the function and regulation of the protein are not known and were examined in this investigation. Our results showed that the hSMVT protein is glycosylated and that this glycosylation is important for its function. Studies utilizing site-directed mutagenesis revealed that the N-glycosylation sites at position Asn(138) and Asn(489) are important for the function of hSMVT and that mutating these sites significantly reduces the V(max) of the biotin uptake process. Mutating the putative PKC phosphorylation sites Thr(286) of hSMVT led to a significant decrease in the PMA-induced inhibition in biotin uptake. The latter effect was not mediated via changes in the level of expression of the hSMVT protein and mRNA or in its level of expression at the cell membrane. These findings demonstrate that the hSMVT protein is glycosylated, and that glycosylation is important for its function. Furthermore, the study shows a role for the putative PKC-phosphorylation site Thr(286) of hSMVT in the PKC - mediated regulation of biotin uptake.